(untitled) (Medico Legal Update, 2023)
Juvenile terrorism, also known as youth or adolescent terrorism. Youth populations have been found to be especially susceptible to recruitment by violent extremist organisations. The causes of juvenile’s terrorism are multifaceted and complex, such as “Push factors” which can be defined as negative circumstances that the child tries to escape by joining the group, while the “pull factors” represent the positive incentives, attracting the children to join the groups. Factors contribute to the radicalization of young individuals, including marginalization, discrimination, and additionally ideological indoctrination, and also feeling lack of disenfranchised in society. Thus to examine and to know factors of Juvenile Terrorism and what are the preventative measure can be enabled in the society. The study is based on secondary data to find out the factors of terrorism. Juvenile terrorists who were brought to FSL Bangalore from different parts of India and examined to psychological behaviour through polygraph examination and showed that juveniles who were in the age group of 14- 17 years were unable to take proper decisions in life and to take proper organisation in their life and showed their susceptible to social influences of the organised group. Therefore providing guidance, counselling and improving communication pathways in family would reduce influences to radicalization.